Strength training: 10 rm vs 30 rm - training load does matter - Ronnestad, B. R.; Ofsteng, S.; Knox, S.; Hammarström, D.; Helkala, K.; Knox, B.; Josok, O.; Hollan, I.; Ellefsen, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: To maximize muscle hypertrophy and strength, heavy loads are often recommended (e.g. Ratamess et al., 2009). However, recent studies have challenged this view and claim that low loads can promote adaptations similar to high-load training, as long as it is performed to volitional fatigue (Burd et al. 2012; Mitchell et al., 2012). In the present study, we investigate the effect of high-load (H) vs. low-load (L) strength-training on maximal strength and lean body mass (LBM), as well as on performance in rapid movements such as counter-movement jump (CMJ) and during an agility test. Method: Twentyseven military students (20±1 years, 75±13 kg, VO2max 58±6 mL/kg/min) with similar circadian rhythm, activity level, and nutrition intake were randomly assigned to high-load (H; 3x10RM, n=14) or low-load (L; 3x30RM; n=13) strength training regimes. Both groups trained the same seven exercises (3 lower body and 4 upper body) twice a week for 9 wks. The effects of the different strength protocols were measured in 1RM (leg press, bench press and biceps curl), agility, CMJ, and dual-energy X-ray absorptiometry assessments of LBM. Results: There were no differences between the groups at baseline. H increased overall 1 RM (Sleg-, bench-press and biceps curl) significantly more than L (17±9% vs. 10±6%, respectively, p 0.05). H had also a larger performance improvement than L in both CMJ (11±7% vs. 5±7%, respectively, p 0.05) and agility (2.1±3.9% vs. -1.2±2.9%, respectively, p 0.05). H had a tendency towards larger increase in LBM of the lower- and upper extremities than L (5.0±3.7% vs. 2.4±3.3%, respectively, p=0.056). Effect size (ES) analyzes reveled moderate effects in favor of H vs L in 1RM, CMJ, agility and LBM (ES: 0.79, 0.78, 0.97, and 0.74, respectively). Discussion: The main finding was that the H protocol improved 1RM, CMJ and agility more than the L protocol and tended to induce a superior increase in LBM, despite both protocols being performed to volitional fatigue, supported by moderate ES in favor of H vs L on all variables. This is in agreement with similar studies (e.g. Campos et al., 2002) and somewhat contrary to other studies (e.g. Mitchell et al. 2012). Indeed both protocols induced strengthtraining adaptations, but when the aim is to maximize performance in rapid movements such as CMJ and agility tests, H training seems to be beneficial.